2010
DOI: 10.1111/j.1467-8268.2009.00228.x
|View full text |Cite
|
Sign up to set email alerts
|

Do International Remittances Affect Poverty in Africa?*

Abstract: International remittances flowing into developing countries are attracting increasing attention because of their rising volume and their impact on recipient countries. This paper uses a panel data set on poverty and international remittances for African countries to examine the impact of international remittances on poverty reduction in 33 African countries over the period 1990-2005. We find that international remittances-defined as the share of remittances in country GDP-reduce the level, depth, and severity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
177
1
9

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 226 publications
(218 citation statements)
references
References 64 publications
31
177
1
9
Order By: Relevance
“…Drawing on Piketty's celebrated literature that has substantially debunked the Kuznets' conjectures to which foreign aid policies have been aligned, we suggest that developed countries should oriented developing nations towards industrialisation by focusing more on inequality and less on economic growth. This is broadly consistent with an evolving narrative on inequality in the continent (Elu, 2013;Mthuli et al, 2014;Brada & Bah, 2014;Asongu et al, 2014;Anyanwu, 2011Anyanwu, , 2014 6 .…”
Section: Concluding Implicationssupporting
confidence: 74%
“…Drawing on Piketty's celebrated literature that has substantially debunked the Kuznets' conjectures to which foreign aid policies have been aligned, we suggest that developed countries should oriented developing nations towards industrialisation by focusing more on inequality and less on economic growth. This is broadly consistent with an evolving narrative on inequality in the continent (Elu, 2013;Mthuli et al, 2014;Brada & Bah, 2014;Asongu et al, 2014;Anyanwu, 2011Anyanwu, , 2014 6 .…”
Section: Concluding Implicationssupporting
confidence: 74%
“…Similar effects have also been reported in cross-country studies by Ravallion and Chen (1997); Adams (2004); Ram (2007); Kanbur (2008); Fosu (2009Fosu ( , 2010; and Anyanwu & Erhijakpor (2010). While testing the claim that in recent times the poor have lost ground, both relatively and absolutely, even when average levels of living have risen, Ravallion and Chen (1997) used household surveys for 67 developing and transitional economies over 1981-1994.…”
Section: Review Of Literaturesupporting
confidence: 53%
“…Typically, investment in this type also contributes to poverty reduction in the short run through increased demand for intermediate inputs, labour, and other factors of production. According to Anyanwu and Erhijakpor (2010), evidence has shown that expenditures for education and health are effective levers of redistribution. More importantly, when public spending on education as well as on health is targeted toward the poor, it can produce a double dividend, reducing inequality and poverty in the short run and increasing the chances for poor children to access formal jobs and thus break free from the intergenerational poverty trap.…”
Section: Variable Description and Data Sourcesmentioning
confidence: 99%
“…Buch and Kuckulenz (2010) find that remittances have a positive impact on welfare enhancing effect, such as consumption, capital investment, education and health. Employing panel data for 33 African countries over the 1990-2005 period, Anyanwu and Erhijakpor (2010) claim that the inflows of remittances have a positive impact on poverty reduction in 33 African countries. This study also argues that the reduction of poverty depends on poverty measurement procedures.…”
Section: Brief Literature Reviewmentioning
confidence: 99%